Decline in age at menarche among Spanish women born from 1925 to 1962 - Barcos Ana; Ederra María; Vidal Enrique; Ascunce Nieves; Cabanes Anna; Erdozain Nieves; Lope Virginia; Pollán Marina (BMC, 2009)
Abstract Background While the timing of reproductive events varies across populations, a downward trend in age at menarche has nevertheless been reported in most of the developed world over the past century. Given the impact of change in age at menarche on health conditions, this study sought to examine secular trends in age at menarche among women living in Navarre (Northern Spain) who participated in a population-based breast cancer screening programme. Methods The study was based on 110545 women born from 1925 to 1962. Trends were tested using a linear regression model, in which year of birth was entered continuously as the predictor and age at menarche (years) as the response variable, using size of town and region of birth as covariates. Results Among women born in Navarre between 1925 and 1962, age at menarche declined steadily from an average of 13.72 years in the 1925-1929 birth-cohorts to 12.83 years in the 1958-1962 birth-cohorts. Controlling for size of town or city of birth, age at menarche declined by an average of 0.132 years every 5 years over the period 1925-1962. This decline was greater in women born in rural versus urban settings. Trends were also different among regions of birth. Conclusion We report a population-based study showing a downward trend in age of onset of menarche among Spanish women born in the period 1925-1962, something that is more pronounced among women born in rural settings and varies geographically.